Stingless bees in coffee: yield gains and assessing neonicotinoid impact - Ramos, Jenifer Dias; Santos, Gustavo Souza; dos Santos, Charles Fernando; De Oliveira Kaminski, Thamires Sá; Cione, Ana Paola; Alves, Denise Araujo; Quenzer, Fernando Celso Longhim; Campbell, Alistair John; Pereira, Andrigo Monroe; Thompson, Helen; Martins de Queiroz, Ana Carolina; Bento, José Maurício Simões; et al. (Frontiers in Bee Science, 2026)
IntroductionCoffee production depends heavily on pollination services, but the combined effects of managed pollinators and pesticide use on crop yield and pollinator health are still poorly understood. This study evaluated the contribution of supplemental pollination by the stingless bee Scaptotrigona depilis to coffee yield and assessed the impact of thiamethoxam, a neonicotinoid insecticide, on colony strength in Brazilian coffee farms.MethodsColonies of S. depilis were introduced into both conventional and organic coffee farms. Coffee yield was measured in branches located near and far from bee colonies. Colony strength parameters were monitored over time, and pesticide residues were quantified in plant tissues (leaves, nectar, pollen) and in bee-collected floral resources.ResultsSupplemental pollination by S. depilis significantly increased coffee yield by 67% in branches closer to the colonies. Low but detectable residues of thiamethoxam and its metabolite clothianidin were found in plant tissues and bee-collected resources. No significant negative effects were observed on brood production or brood mortality in colonies located in conventional farms compared to those in organic farms. Foraging activity differed between farm types before exposure to coffee bloom but normalized over time.DiscussionManaged stingless bees can markedly enhance coffee production without experiencing measurable detrimental effects under current label-compliant neonicotinoid use. These findings offer practical insights for developing more sustainable coffee production strategies that align productivity with pollinator health and conservation.